Highway to Controversy: The Maine Turnpike and the Way Life Should Be - Colgan, Charles (Maine Policy Review, 1997)
Whether to widen the Maine turnpike has been a source of heated debate for many years and, despite extensive study to clarify the issue, it remains polarized. Proponents argue that widening is critical to the economic health of the state. Opponents argue that widening will not resolve congestion problems over the long haul and advocate for alternatives such as peak-hour tolls. Charles Colgan traces the events leading up to the current impasse, covering the arguments for and against widening and summarizing the extensive study of the issue. He concludes that widening is necessary but irrelevant to the larger debate at hand, which will not be resolved by a six-lane or four-lane turnpike.
Keywords: Maine Turnpike